(3eYGQL Gdage aj TQM GdfXes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG ChdGfG ef GdJhajb(B... (3CeG HYO, aEfg deG habfG Gddg JYGdi (B... (3ef EedGA ebOeI aj Yde GdcdGe(B... (3QCjfG Cf fedj dgG TQMG(B...s
(3BNQgG (B:s
(3aGdJhHI hGLHI, CeG GdeYUjI GdUZjQI aChLH GdJhHI YfgG HGdSeY hCHh Ydj ChLHgG CjVG(B... (3agPG BNQ eG CQOfG HjGfg(B...s
(3JHUQI GdYfhGf (B:s
(3aj GdgOjI(B: (3eWGQM Gdages
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B285s
Keywords: (3GdJhMjO hGdedd hGdfMds